IMPLEMENTASI TAKSONOMI BLOOM PADA MATA KULIAH KEWIRAUSAHAAN, KOMPETENSI DOSEN TERHADAP NIAT BERWIRAUSAHA MAHASISWA - Ruslaini Ruslaini; M. Chaidir; Ngadi Permana (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
This research aims to 1) determine the effect of Bloom’s Taxonomy in entrepreneurial course on students’ entrepreneurial intention; 2) determine the effect of Lecturer Competence on students entrepreneurial intention; 3) determine the effect of Bloom’s Taxonomy and Lecturer Competence simultaneously on students’ entrepreneurial intention.The research method used is quantitative method with 120 research respondents obtained based on purposive sampling technique. Data were collected using a questionnaire instrument. The analysis technique used is multiple linear regression analysis.The results of this study suggest that there is an effect of implementing Bloom's Taxonomy in entrepreneurship courses on students' entrepreneurial intention with a t-score of 2,630, an effect of lecturers' competence on students' entrepreneurial intention with a t-score of 2,908. Furthermore, there is an effect of implementing Bloom's Taxonomy and Lecturer Competence simultaneously on students' entrepreneurial intention.